7 Maestros, 7 Materiales. - Chavez Mendoza, Alvaro (Colombia : s.n., 1995)
Munoz De Vargas, Aura ; Sandoval, Eduardo ; Ruizez, Otilia ; Trespalacios, Guillermo ; Munoz Erki Narvaez, Eduardo ; Sanchez, Carlos ; Ruiz, Maria and Rafael ; Guacamayas Community ; Waunana Indigenous Community ; Community of San Jacinto ; South of Cauca
7 Materiales : Ceramics, Jewelry, Barniz de pasto, Inlaid works in fuzz, Inlaid works in bone and tortoise shell, Baskery, Weaving
Gift Flanders DC
boek